Health Education on Diarrhoea Disease Prevention and Hand Washing Demonstration with Competition for School-Aged Children - Nanda Desreza; Tria Agustini; Nelly Nelly (CV. Proaksara Global Transeduka, 2025)
Diarrhoea is a disease characterised by changes in the shape and consistency of soft to liquid stools and an increase in the frequency of bowel movements more than 3 or more times a day which may be accompanied by vomiting or bloody stools. The method of implementing this activity is diarrhoea counselling, discussion, question and answer, pre-posttest, demonstration and hand washing competition. Based on the results of a survey that has been conducted, there are still school-age children in Cot Mancang village who do not know about diarrhoea and how to wash hands 6 steps properly and correctly. Activities carried out to 24 school-age children who attended the health education event. With this activity, it is hoped that it can trigger awareness of school-age children to wash their hands. This community service activity may be a good forum for the Cot Mancang village community, especially for school-age children to increase motivation about diarrhoea and how to wash hands 6 steps properly and correctly.